Proyecto de factibilidad para la creación de una empresa de repostería saludable en el sector Solanda, Quito. - Calvopiña Pacheco, Silvana Gabriela (2024)
The venture focused on evaluating the possibility of establishing a healthy bakery in Solanda, Quito, motivated by concern about the proliferation of unhealthy desserts. According to data from the tenth edition of the Diabetes Atlas, 537 million adults (between 20 and 79 years old) live with diabetes, which highlighted the need to offer more beneficial food alternatives. The proposal consisted of making desserts using almond flour and fruits, taking advantage of their nutritional properties. According to the World Health Organization, in 2002, 16.7 million people died from cardiovascular diseases, which are one of the main causes of death worldwide, largely due to the consumption of saturated fats. The results of the research, based on surveys, revealed that 92.5% of the population would be interested in consuming natural desserts. Also, financial analysis indicated that, at a price of $2.88 per 120 grams, the project would have an NPV of $4.448,54 and an IRR of 33%, and a payback period of 2 years and 8 months, confirming economic viability. This project highlights the existence of a potential market in Solanda for healthy confectionery products, demonstrating that the creation of such an enterprise is feasible both commercially and financially.